Idioms as Cultural Commonplaces: Corporeal Lessons from Hokkien Idioms - Sue Hum (Journal of the Assembly for Expanded Perspectives on Learning, 2005)
This essay uses idioms, especially Hokkien idioms, to counter the western predisposition of separating mind and body, arguing that they underscore the mind-body shift that occurs with the acquisition of academic discourses.